2022
DOI: 10.22161/ijeab.74.18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Direct Investment on Nigeria’s Agricultural Sector (1981 to 2019)

Abstract: The need to augment the financial policy interventions of the Central Bank of Nigeria in the agricultural sector is sine qua non. Since agriculture is still the mainstay of Nigeria’s economy, its reliance on foreign direct investment (FDI) ought to be ascertained. Consequently, this study investigated the impact of foreign direct investment on Nigeria’s agricultural sector. Time series data between 1981 and 2019 were obtained from the databases of the Central Bank and Food and Agriculture Organisation. The Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The coefficient of Foreign Direct Investment in Agriculture (FDIA) was negative (-22.930) and significant, showing that the variable exhibits negative link with agricultural output in the long term. This result is in line with Ogbanje & Salami (2022) who stated that FDIA had significant and negative influence on the agrarian output in Nigeria. The coefficient of Agricultural Public Investment (PAI) was positive (24.700) and significant at 0.01% probability level which infers that agricultural growth in Nigeria is positively influenced by public investment made in the sector in the long run.…”
Section: Single Equation-error Correction Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficient of Foreign Direct Investment in Agriculture (FDIA) was negative (-22.930) and significant, showing that the variable exhibits negative link with agricultural output in the long term. This result is in line with Ogbanje & Salami (2022) who stated that FDIA had significant and negative influence on the agrarian output in Nigeria. The coefficient of Agricultural Public Investment (PAI) was positive (24.700) and significant at 0.01% probability level which infers that agricultural growth in Nigeria is positively influenced by public investment made in the sector in the long run.…”
Section: Single Equation-error Correction Modelsupporting
confidence: 91%
“…Therefore, the bank credit is a channel through which the Nigerian government can achieve a boost in the output of the agricultural sector. Ogbanje and Salami (2022) studied the influence of FDI on Nigeria's agricultural sector. Augmented Dickey-Fuller test displayed that the variables were I(1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With OLS, Agunuwa et al (2015) showed that there was a positive association between commercial banks' credit and agricultural productivity in Nigeria. Ogbanje et al (2010) examined the effect of commercial banks' loan on agricultural GDP in Nigeria from 1981 to 2007 and stated that commercial banks' loan had a significantly positive effect on agricultural GDP applying simple regression. Osuji and Chigbu (2012) studied the impact of financial development on economic growth in Nigeria from 1960 to 2008 using Granger causality testing and the error correction method.…”
Section: Impact Of Bank Credit On Agriculturementioning
confidence: 99%
“…(2015) showed that there was a positive association between commercial banks’ credit and agricultural productivity in Nigeria. Ogbanje et al. (2010) examined the effect of commercial banks’ loan on agricultural GDP in Nigeria from 1981 to 2007 and stated that commercial banks’ loan had a significantly positive effect on agricultural GDP applying simple regression.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nigeria has the largest population and economy in Africa (Ismail and Kabuga, 2016). With agriculture as the major occupation, Nigeria is located between latitudes 4º 16 and 13º 53 N and longitudes 2º 40 and 14º 4′ E. The climate varies with Equatorial Guinea in the South through the Guinea savannah in the central region and dry Sahel savannah in the North (Hamzat et al, 2006;Ogbanje and Salami, 2022). Climate change is evident in Nigeria by way of rising temperature, varying rainfall, rising sea level and seasonal flooding, drought and desertification (Haider, 2019).…”
Section: Methodsmentioning
confidence: 99%